(untitled) (TAMADDUN NURI JURNALI, 2024)
Tussi shows that the understanding of appearances arising from the various natures of things can only be in stages, and that he connects the real existence and development of the objectively existing phenomena and processes in reality with the mind, the ambivalence he called clarity in the theory of epistemology, and he This article analyzes the unity of intuition, which is called gnosis.